A simple PCR method for sexing Japanese quail Coturnix japonica at hatching. Issue 1 (2nd January 2017) - Coustham, V.; Godet, E.; Beauclair, L.
ABSTRACT: 1. The quail is a potentially important avian model for molecular studies; a major drawback is the inability to sex visually before 3 weeks of age. Molecular sexing is therefore an absolute requirement when animals are sampled before that age. 2. A low-cost method using common laboratory equipment based on Allele-Specific Multiplex-Polymerase Chain Reaction was developed to undertake reliable molecular identification of the sex of Coturnix japonica directly at hatching. 3. This simple method works with down feathers collected from behind the neck of the newly hatched quail and includes internal controls during the PCR to limit risks of error. Males and females can be discriminated on the basis of the presence of one or two amplicons, respectively.